Artificial Intelligence in Tourism: Opportunities and Challenges Seen by Travelers (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Integrating artificial intelligence (AI) into tourism becomes increasingly impactful for consumer behavior. We investigated the impact of AI on the tourism industry and the opportunities and challenges for travelers and service providers. Using a qualitative method, a structured questionnaire was created to explore the perceptions of travelers and industry stakeholders regarding AI integration. Data were collected through in-depth interviews with participants who had engaged with AI-enhanced services in tourism. The results revealed how AI technologies have reshaped travel experiences, service efficiency, and customer satisfaction. The results contribute to the understanding of AI's role in the tourism industry and provide a foundation for future research on effective strategies for AI implementation in tourism.